(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Echocardiography, as an important method for examining the heart, is undergoing significant changes, moving from research phases to widespread clinical use. New technological advances, including improved image resolution and the development of data analysis software, are opening new horizons in the diagnosis and monitoring of cardiovascular diseases. [1] This abstract discusses recent developments in the field of echocardiography, their impact on clinical practice and future developments. Particular attention is paid to the transition from research data to real-world application in clinical practice, and how this may impact the diagnosis, treatment and prognosis of cardiovascular disease outcomes.[5]